PENGARUH DIGITALISASI, RELIGIUSITAS DAN KUALITAS PRODUK TERHADAP KEPERCAYAAN MEREK SERTA IMPLIKASINYA PADA KEPUTUSAN PEMBELIAN PRODUK-PRODUK HALAL - Muhammad Aria Wahyudi; Zara Tania Rahmadi (Rekaman : Riset Ekonomi Bidang Akuntansi dan Manajemen, 2022)
Consumption has great urgency in every human life. There is no life for humans without consumption. Therefore, economic activity leads to the fulfillment of consumption demands for humans. Neglecting consumption means neglecting life and also neglecting man's enforcement of his duty. Since the pandemic, consumer behavior has experienced a mass shift from manually transacting to digitally because it is supported by activity restrictions imposed by the government, so that the dependence of both consumers and business actors on digital technology has never been as great as it is today. The rapid and widespread digitalization process has made many companies give birth to new digital platforms to meet the needs of the community. The presence of digital platforms is one of the consequences of the digitalization process that humans must do today. Without digitalization, human activities in various fields will be left behind, especially in the current pandemic conditions which severely limit various activities and interactions. Based on the results of the study, it was found that almost all respondents had doubts about all purchasing decisions for the consumption of halal products. Respondents have doubts in checking the packaging of halal products purchased 59%, hesitant in distinguishing 53.8% of halal labels, check halal certificate numbers on products purchased 46% and confidence in halal labels on product packaging without checking on the website 54.4% . Meanwhile, knowing MUI as a product label marker declared halal 63.4%. So it can be concluded that this initial research indicated positive non-linear brand trust that the brand was believed to be halal